Development and validation of the Zadrian-Ifdil Problem Checklist (ZIPC) for college students - Zadrian Ardi; Ifdil Ifdil; Maysitoh Maysitoh (Indonesian Institute For Counseling, Education and Therapy, 2020)
The variety of problem conditions and the specific dynamics of college student demographics demands a holistic measurement. Various measurements to reveal the attributes of students' problems have been developed in Indonesia, but they are not optimal because they are still partial. Even though a holistic measurement tool has been developed, its effectiveness is still a matter of debate, especially in measuring instrument duration and the number of items that are too large. The development of the Zadrian-Ifdil Problem Checklist (ZIPC) measuring instrument aims to obtain an effective and efficient measuring tool in identifying problems experienced by students daily. This study consists of three phases: item development, testing, validation, and item revision. The sample involved in this study were 639 people spread all over Indonesia. Analysis and validation of measuring tools using the Rasch model approach. The development and validation results revealed that the student version of ZIP-C was reliable and valid to reveal daily personal problems in 8 variables of problem conditions and 50 items. This measuring tool can be used for research purposes and practice services and mental health interventions by professionals.